Thoreau's Importance for Philosophy. - Furtak, Rick Anthony (American philosophy, 2012)
Although Henry David ThoreauGs best-known book, Walden, is admired as a classic work of American literature, it has not yet been widely recognized as an important philosophical text. In fact, many academic philosophers would be reluctant to classify Thoreau as a philosopher at all. The purpose of this volume is to remedy this neglect, to explain ThoreauGs philosophical significance, and to argue that we can still learn from his polemical conception of philosophy. Thoreau sought to establish philosophy as a way of life and to root our philosophical, conceptual affairs in more practical or exist.